2010
DOI: 10.1111/j.1747-0765.2010.00503.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of preceding compost application on the nitrogen budget in an upland soybean field converted from a rice paddy field on gray lowland soil in Akita, Japan

Abstract: The annual nitrogen (N) budget was measured in a soybean-cultivated upland field during the first year after conversion from a paddy field on gray lowland soil, which is typically found on the Sea of Japan side of northern Japan. Forage rice was cultivated on lysimeter fields for 4 consecutive years with applications of chemical fertilizer, immature compost, or mature compost (the control, immature compost, and mature compost plots, respectively), and then the fields were converted to upland fields for soybean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 22 publications
2
27
0
Order By: Relevance
“…Therefore, the nitrogen budget of soybean cultivation in a rotated paddy field could be negative, indicating nitrogen loss from the field. In fact, negative nitrogen budgets were reported recently in Japanese soybean-cultivated upland fields during the first year after conversion from paddy fields (−10.0 g N m −2 year −1 in Akita [8], −4.0 g N m −2 growing period −1 in Shiga [9]). …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the nitrogen budget of soybean cultivation in a rotated paddy field could be negative, indicating nitrogen loss from the field. In fact, negative nitrogen budgets were reported recently in Japanese soybean-cultivated upland fields during the first year after conversion from paddy fields (−10.0 g N m −2 year −1 in Akita [8], −4.0 g N m −2 growing period −1 in Shiga [9]). …”
Section: Introductionmentioning
confidence: 99%
“…In another study, soybean showed a greater rhizosphere priming effect on total soil C efflux as compared with wheat (Triticum aestivum L.) (Cheng et al 2003). Annual N budgets in an upland soybean field converted from a paddy rice field on gray lowland soil were negative, ranging from -14.2 to -6.4 g N/m 2 , because a large quantity of N was removed from the field with harvested soybeans (Takakai et al 2010). In contrast, the N budgets in paddy rice fields (rice cultivation) have been shown to be even or positive (App et al 1984, Kyuma 2004.…”
Section: Short-term Upland Rotation R S R R R S R S R R S R S S R R Smentioning
confidence: 93%
“…All treatments were conducted with one replication (lysimeter). More detailed information is provided in related papers [17,18]. The chemical properties of studied soils (0-10 cm) in each plot are provided in detail by Takakai et al [17].…”
Section: Site Description and Plant Cultivationmentioning
confidence: 99%
“…More detailed information is provided in related papers [17,18]. The chemical properties of studied soils (0-10 cm) in each plot are provided in detail by Takakai et al [17]. Briefly, the soil pH and cation exchange capacity (CEC) ranged from 5.6 to 6.0 and 21.8 to 23.9 cmol C kg −1 , respectively.…”
Section: Site Description and Plant Cultivationmentioning
confidence: 99%
See 1 more Smart Citation